Developing know-how to deal with trash: Analysis of an online pedagogical practice in times of pandemic - Souza, Débora Elisa de; Ticle, Erika Mara Nogueira de Santana; Monteiro, Julia Amorim; Nascimento Junior , Antonio Fernandes (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
This paper aims to analyze a pedagogical practice seeking to understand its potential for promoting a critical reflection on the topic of Waste. The practice was developed within the scope of the discipline of Science and Decolonizing Cultures offered in the Remote Teaching model, due to the COVID-19 pandemic, in the Graduate Program in Scientific and Environmental Education of a Federal University. For this, evaluations made by scholarship holders of the Institutional Program of Initiation to Teaching scholarships were taken as data, who after watching the video, answered the following question: what are the positive points and points to be improved in practice. Therefore, this work fits into the Qualitative Research Methodology and the responses were analyzed using Content Analysis and, more specifically, thematic categorization. After the analysis, it was possible to find three categories which are: “Poem as an enhancer of practice”, “Transdisciplinary approach” and “Problematization”. Thus, it is possible to consider that the practice fulfilled its role to promote a critical reflection on the theme of garbage since it was based on Critical Environmental Education and brought art to problematize issues related to the theme, causing contextualized reflections that transcend how the theme is commonly addressed.